Antimicrobial activities of leaf extracts of Abelmoschus Ficulneus(l) Wight & Arn., Malvaceae - S. KALPANA; V.THANGAPANDIAN (International Journal of Pharma and Bio Sciences, 2017)
The present study was carried out using disc diffusion method to evaluate the antimicrobial property of Abelmoschus ficulneus (L) Wight & Arn. (Malvaceae) leaves against certain bacterial and fungal stains causing infection. Petroleum ether, chloroform, ethyl acetate and methanol extracts were obtained by soxhlet method and aqueous extract was obtained by hot aqueous extraction method. Leaf extracts were tested for the inhibition activity against ten bacterial stains Staphylococcus aureus, Enterococcus faecalis, Bacillus thuringiensis, Streptococcus pyogenes, Bacillus subtilis, Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumonia, Proteus mirabilis, Salmonella paratyphi, six fungal stains Trichoderma viride, Aspergillus fumigates, Mucor spp, Azospirillum lipoferum, Penicillium spp. and Candida albicans. Ampicillin 10 mcg/disc and tetracycline 10 mcg/disc were used as standard antibiotics against bacteria and fungi, respectively. The aqueous and methanol leaf extracts of the selected plant possessed significant antibacterial and antifungal activities.